1998
DOI: 10.1097/00005537-199812000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in children with major craniofacial anomalies

Abstract: The likelihood for surgical airway management is related to specific craniofacial diagnosis. The length of tracheal cannulation is greatest for infants and young children who manifest severe airway compromise, often because of nasal obstruction in combination with other anatomic factors. Early tracheotomy is advocated for these patients to promote optimal growth and development. Choanal atresia is often misdiagnosed in these infants; nasal obstruction is actually secondary to midface retrusion. Staged surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 11 publications
(17 reference statements)
7
77
0
2
Order By: Relevance
“…Early tracheotomy is advocated for these infants. Approximately 20% of children with syndromes involving bony deformities of the face and skull unambiguously required tracheotomy, as reported by Sculerati et al [29]. …”
Section: Discussionmentioning
confidence: 97%
“…Early tracheotomy is advocated for these infants. Approximately 20% of children with syndromes involving bony deformities of the face and skull unambiguously required tracheotomy, as reported by Sculerati et al [29]. …”
Section: Discussionmentioning
confidence: 97%
“…Most of the patients with craniofacial anomalies require airway management ranging from prone positioning to tracheotomy and DO 11 . DO is accepted as a reliable surgical technique and an alternative to tracheotomy for long-term management of the airway 11,12,13 . It has been observed that DO reduces the need for tracheotomy especially in pediatric patients and allows for early decannulation in patients who previously underwent tracheotomy 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…(d) Tracheostomy may be necessary in some infants with bilateral CA. 10 However, this is an invasive procedure.…”
Section: Discussionmentioning
confidence: 99%